Evaluation of the legumes from genus Trifolium - Moraes, Carlos Otávio Costa (2014)
From March 1984 to November 1985, in the Agricultural Experiment Station of the Federal University of Rio Grande do Sul, Guaíba, RS, Brazil, the potential of the native species T. riograndense Burkart and T. polymorphum Poir., were evaluated in comparison with white clover (Trifolium repens L). cultivars BR-1-Bagé, Regal, Jacuí and Guaíba. The variables dry matter yield (DM), HCN content, nodulation, persistence, yield, crude protein (CP), percentage and in vitro dry matter digestibility (IVOMD) and in vitro organic matter digestibility (IVOMD) were evaluated. The white clover cultivars showed variations and the new cultivars presented very promising. The native species T. riograndense (2x and 4x) and T. polymorphum presented low DM yield, but showed good quality and, according to the contents of HCN achieved, showed that probably are not cyanogenic. The autotetraploid form of T. riograndense was not significantly superior to the diploid form of the some specie for none of the variables studied.